Expand (1+x)^3. Express (1+i)^3 in the form a+bi. Hence, or otherwise, verify that x = 1+i satisfies the equation: x^3+2*x-4i = 0.

First, we factor out one (x+1). (1+x)^3 = (x+1)^2(x+1)= Then, we expand using the formula (a+b)^2 = a^2 + 2ab +b^2: =(x^2+2x+1)(x+1)= Then we multiply: = x^3 + 2x^2 + x + x^2 + 2x + 1 We sum the terms with the same power and we get: (1+x)^3 = x^3 + 3x^2 + 3x +1. For the next part, we expand using the formula we just calculated: (1+i)^3 = i^3 + 3i^2 + 3i + 1 = We replace i^2 with -1: = -i -3 +3i +1 Next, we bring this to the a+bi form: (1+i)^3 = 2i-2. To check if x = i+1 is a root of that equation, we replace x with i+1 and see if the result is 0: (1+i)^3 + 2(1+i) - 4i = We use the form of (1+i)^3 which we calculated above and expand the bracket: 2i-2 + 2i+2 -4i = 0.

Related Further Mathematics A Level answers

All answers ▸

The rectangular hyperbola H has parametric equations: x = 4t, y = 4/t where t is not = 0. The points P and Q on this hyperbola have parameters t = 1/4 and t = 2 respectively. The line l passes through the origin O and is perpendicular to the line PQ.


Find the derivative of the arctangent of x function


How can we solve a limit having an indetermination of the type 0/0 or infinity divided by infinity?


What is the polar form of the equation: x^2+y^2 =xy+1


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences